THE EMERGENCE OF FOREIGN INTERVENTION AGAINST HUMAN RIGHTS VIOLATIONS IN ARMED CONFLICT IN A STATE - Mahfud SH (Fakultas Hukum Universitas Mataram, 2013)
The violation on the law of war and human right regulations may cause foreign (international) intervention on every war violations, if violating country does not implement the law enforcement for the violating criminal. The international interventions to punish the violating actor (of the law of war and of human right) happening in a military conflict will occur if the national court of the country is unwilling and unable to punish the prisoner of war . Key word ; The Violation of the Law of War and Human Right, War Criminal